Sinners for Love: A Screenplay Exploring the Destructive Nature of Obsessive Love - Princessa Nathania Yuwono; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This thesis is created with the purpose to explore the destructive nature of obsessive love from its reasonings, symptoms, and how it affects people around the perpetrator. While love is a widely-known emotion that has been a norm for everyone, many still do not know the dark side of too much love, which can be the result of mental illnesses such as obsessive love disorder and many more. Obsessive love disorder itself is a mental disorder where someone has an overwhelming obsessive desire to possess and protect another person. Using screenplay as the form and drama-thriller as its genre, I will show the development and symptoms of obsessive love disorder through Sinclair as the main character. She will also show how she manipulates people around her to fulfill her love obsession. In the screenplay, Sinclair will manipulate Charlot’s love for her by using him to get the man she obsessively loves.